EFFECT OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION (CASE STUDY AT PERUMDA TIRTA MANGKALUKU, PALOPO CITY) - Firman Salam, Muhammad; Sumardi, Sumardi; Sudirman, Indrianty (Scientium Management Review, 2022)
This study aims to determine the effect of work environment and compensation on employee performance through work motivation at Perumda Tirta Mangalauku, Palopo City. This research is a quantitative research, the data used is primary data, namely data obtained from distributing questionnaires to research objects. The population in this study were employees at Perumda Tirta Mangkaluku, Palopo City. The sampling technique used purposive sampling with a total sample of 75 respondents. The analytical method used in this study is regression analysis via SPSS version 2.3. The results of the study show that (1) the work environment has a positive and significant effect on work motivation; (2) compensation has a positive and significant effect on work motivation; (3) the work environment has a positive and significant effect on employee performance; (4) compensation has a positive and significant effect on employee performance; (5) work motivation has a positive and significant effect on employee performance; (6) the work environment has a positive and significant effect on employee performance through work motivation; and (7) compensation has a positive and significant effect on employee performance through work motivation.